2006
DOI: 10.1002/uog.2731
|View full text |Cite
|
Sign up to set email alerts
|

Predicting operative delivery

Abstract: Objective Unplanned operative delivery (vaginal or abdominal)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 27 publications
2
57
3
1
Order By: Relevance
“…No beneficial effect of anterior occiput position could be detected in predicting successful IOL as well. It seems that clinical models with combined consideration of maternal factors and ultrasound measurements are needed for a proper prediction of successful vaginal delivery for each individual [42, 43]. …”
Section: Discussionmentioning
confidence: 99%
“…No beneficial effect of anterior occiput position could be detected in predicting successful IOL as well. It seems that clinical models with combined consideration of maternal factors and ultrasound measurements are needed for a proper prediction of successful vaginal delivery for each individual [42, 43]. …”
Section: Discussionmentioning
confidence: 99%
“…Molina et al [7], among other authors [13,14], evaluated the reproducibility of the different ultrasound parameters used to assess the evolution of delivery and concluded that the angle of descent is the most reproducible parameter for measuring fetal head progression during labor, whereas Duckelmann et al [10], showed that the determination of this ultrasound parameter is also independent of the professional's experience.…”
Section: Spontaneous Vaginal Delivery Occurred In 72 (71%) Women Insmentioning
confidence: 99%
“…76 In a prospective observational study with 202 term nulliparous women, they identified that factors, such as maternal age, history of cesarean section, Bishop score and bladder position on valsalva had an ability of up to 87% to discriminate between normal vaginal delivery and operative delivery. The initial ultrasound parameters taken into account were Anterior vaginal wall relaxation determined by translabial ultrasound after bladder emptying, 77 the descent of the bladder wall (the lowest point reached by any part of the bladder) observed on maximal Valsalva maneuver, ultrasound engagement of the fetal head and cervical length determined translabially.…”
Section: Prediction When Planning Spontaneous Labormentioning
confidence: 99%
“…Most likely a combined approach using combinations of maternal factors, sonographic and clinical assessments would offer the expected outcome. 76,89,95,102 …”
Section: Prediction When Planning Induction Of Labormentioning
confidence: 99%